Reframing mergers and acquisitions around stakeholder relationships : economic, political and social processes - Segal, Simon (Journalist) (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Among the significant repercussions of the coronavirus pandemic is escalating public questioning of the desirability and sustainability of the market economy and the societal role of business. These concerns are linked to merger and acquisition (M&A) activity, with significant disruptive consequences for stakeholder relationships and their management. This book explores these changes, moving away from the traditional focus on the financial and strategic aspects of M&A and its rational, technocratic approach. Viewing M&A activity as economic, political, and social (EPS) processes, Segal provides a dialectic understanding of stakeholder relationships around M&A activity and challenges the view that M&A activity is static, linear, and predictable. He develops a conceptual framework to enable practitioners, researchers and policymakers to identify, understand and address the stakeholder and management implications of M&A activity. This is applied to four case studies that make explicit how complex stakeholder relationships play out around M&A and how these power dynamics were managed with different balances. Useful for academics, researchers, managers, advisors, investors, analysts, and other stakeholders, this book highlights the need to understand the EPS implications and processes involved around M&A"--
OCLC-licensed vendor bibliographic record.
Keywords: Consolidation and merger of corporations; Stakeholder management; BUSINESS & ECONOMICS / Mergers & Acquisitions